Measuring the Efficiency of Islamic Financing Modes Using Data Envelopment Analysis: Evidence from Al Salam Bank, Adrar (2020–2023) (Journal of Economic Additions, 2025)
This study applies Data Envelopment Analysis (DEA) to assess the efficiency of Islamic financing modes at Al Salam Bank in Adrar, Algeria (2020–2023). It evaluates Murabaha, Mudarabah, Ijarah, Salam, and Istisna using input-oriented models with constant and variable returns to scale. Results show that while some modes faced inefficiency due to underutilized outputs, Mudarabah for institutions and Murabaha for individuals consistently achieved full efficiency. Efficiency trends were shaped by scale effects and operational changes. The findings provide guidance on optimizing resource allocation, enhancing Islamic financing performance, and offer empirical insights from a branch-level view in an emerging market.Jel Classification Codes: G21, G24, C61, D24, O16
Keywords: Islamic banking, efficiency, Data Envelopment Analysis, financing modes, branch-level analysis, Algeria, Al Salam Bank, CRS, VRS.